2017
DOI: 10.3847/1538-4357/835/2/257
|View full text |Cite
|
Sign up to set email alerts
|

Dust-deficient Palomar-Green Quasars and the Diversity of AGN Intrinsic IR Emission

Abstract: To elucidate the intrinsic broadband infrared (IR) emission properties of active galactic nuclei (AGNs), we analyze the spectral energy distributions (SEDs) of 87 z 0.5 Palomar-Green (PG) quasars. While the Elvis AGN template with a moderate far-IR correction can reasonably match the SEDs of the AGN components in ∼ 60% of the sample (and is superior to alternatives such as that by Assef), it fails on two quasar populations: (1) hot-dust-deficient (HDD) quasars that show very weak emission thoroughly from the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 172 publications
12
119
0
Order By: Relevance
“…Since Elvis et al (1994) published their SED template for unobscured type-1 (broad-line) quasars, there have been multiple studies that have confirmed the uncanny accuracy of this work (e.g., Richards et al 2006;Shang et al 2011;Runnoe et al 2012;Hanish et al 2013;Scott & Stewart 2014;Lyu et al 2017). As a result, we can take the intrinsic SED of a type-1 quasar to be well-understood from the soft X-ray to ∼10 μm.…”
Section: Template For Agn Soft X-ray/uv/optical Emissionmentioning
confidence: 75%
See 4 more Smart Citations
“…Since Elvis et al (1994) published their SED template for unobscured type-1 (broad-line) quasars, there have been multiple studies that have confirmed the uncanny accuracy of this work (e.g., Richards et al 2006;Shang et al 2011;Runnoe et al 2012;Hanish et al 2013;Scott & Stewart 2014;Lyu et al 2017). As a result, we can take the intrinsic SED of a type-1 quasar to be well-understood from the soft X-ray to ∼10 μm.…”
Section: Template For Agn Soft X-ray/uv/optical Emissionmentioning
confidence: 75%
“…However, as suggested in Section 3.1 of Lyu et al (2017), the host contribution in the infrared 8-1000 μm range could be underestimated by merely focusing on the mid-IR spectral features. This argument is based on the different IR SED behaviors of the AGN and the host galaxy: the IR output of an AGN is peaked in the mid-IR but drops quickly in the far-IR, while the galaxy emission is relatively weak in the mid-IR but strong in the far-IR.…”
Section: The F Agn Mir -F Agn Tir Relationmentioning
confidence: 99%
See 3 more Smart Citations